Development of an Observational Parental Scaffolding Measure for Youth with Spina Bifida. (22nd June 2020) - Winning, Adrien M; Stiles-Shields, Colleen; Driscoll, Colleen F Bechtel; Ohanian, Diana M; Crowe, Autumn N; Holmbeck, Grayson N
Abstract: Objective: To examine the reliability and validity of a new observational measure of parental scaffolding, as well as the impact of parental scaffolding on academic and social outcomes among youth with spina bifida (SB). Methods: As part of a larger study, 137 families of youth with SB participated in family interaction tasks and self-report questionnaires at the baseline assessment. Teachers also reported on youth's academic independence and competence, as well as social skills. Guided by previous research and theoretical formulations, a rational approach to measure development was employed whereby maternal and paternal scaffolding composites were created using the Family Interaction Macro-coding System (Holmbeck, Zebracki, Johnson, Belvedere, & Hommeyer (2007) . Parent-child interaction macro-coding manual. Unpublished coding system . Chicago: Loyola University Chicago). Results: The scaffolding measure demonstrated acceptable interrater and scale reliabilities. Additionally, both the maternal and paternal scaffolding composites were significantly associated with scores from self-report questionnaires of parenting behaviors in the expected directions. Maternal scaffolding was positively associated with IQ, academic competence, academic independence, and social self-control in youth with SB, whereas paternal scaffolding was positively associated with social cooperation and social self-control. Differences in scaffolding emerged between mothers and fathers, as well as across demographic variables. Conclusion: Initial findings support the use of the scaffolding measure. Future research should continue to examine the utility of this scaffolding measure in families of youth with SB.